O sentido da alfabetização para professores alfabetizadores da Rede Municipal de São Paulo na vigência do currículo da cidade - Santos, Jonathan José dos (2023)
This research aimed to investigate the meaning teachers attribute to literacy while using the Curriculum of the City of São Paulo and what their practices are to propose suggestions to announce a teacher training based on the propositions of Paulo Freire’s critical literacy pedagogy. Qualitative approach was used, based on Lüdke & André (1986), Bogdan & Biklen (1994) and Chizzotti (2000). Data collection used semi structured interviews and analysis of institutional and school documents. The participants were teachers who work in literacy classes at a public school located in the south zone of the city of São Paulo. This school was especially chosen because it showed satisfactory results in students’ literacy. Data provided by the interviews and documental analysis showed that the teachers did not take part in the elaboration of the Curriculum of The City, which they consider to be a proposition of difficult comprehension. They also did not receive any training to learn how to work with the document proposed by the Education Department of the City. Literacy practices developed by the teachers prioritize activities about the language system based on synthetic or analytical methods learned in previous teaching and training experiences. It was also verified that the Curriculum of the City is largely detached from the perspective of critical literacy proposed by Paulo Freire. In face of such evidence, this study proposed suggestions for teacher training about literacy based on Paulo Freire’s critical literacy propositions